Entre Marias e Joões, muitas representações: o ensino de história e a construção das masculinidades e feminilidades nas revistas femininas nas décadas de 1940, 1950 e 1960 - Gianluppi, Anna Carolina Torezani Ronda (2021)
The male and the female are woven into our mentalities from representations inscribed in our culture and in the products it creates. In this work, the female and male representations will be analyzed throughout the 1940s, 1950s and 1960s. For this, we will use the material published in magazines aimed at the female audience, in particular, The Cruzeiro and Journal of the Girls, understood here as behavior influencers. Our objective is to paper, in the classroom, how the roles of Woman and Man were constructed over time, their ruptures and their permanence. It is also intended to identify, as a counterpoint, the ways in which the feminist movement has acted as an influence on female and male behavior; in accepting the presence of women in public environments and in the labor market; as well as on the standard maternity and femininity models. The research will be based on the discussions of authors such as Joan Scott, Simone de Beauvoir, Margareth Rago, Maria Izilda Matos, Joana Maria Pedro, and Carla B. Pinsky. The study of the columns of women's magazines (The Cruzeiro and Journal of the Girls) will be carried out by analyzing the Memory Box, made available for each decade studied. Each box will contain the following historical variable sources: Newspaper; Fashion; Music, Film and Important Personalities; Advertisements and Column Excerpts. All material is available for student analysis on a website created for the activity. The work presented here is part of the class-workshop presented by the historian Isabel Barca, who argues that the teacher should be the mediator of knowledge. And that it is up to the students to be protagonists of their learning. At the end of the study of all the material, we propose that male and female students choose the decade that most aroused their curiosity to develop a Lapbook (folding book in the style of a 3-dimensional mental map) with the main information on male stereotypes and female of the decade that was chosen. The main objective of the work is to make the students understand that certain behaviors, now naturalized, were created and reaffirmed over time, and that they remain present in our society. And that such behaviors are, therefore, among the generators of several problems faced in our current reality. And it's up to them and them to break the bonds of what it means to be a Man and a Woman in the 21st century.